Cognitive autonomy differences among adolescents in Malaysia - Abderrahim Benlahcene; Sana Anwar Lashar; Anita Lubana (Universitas Muhammadiyah Sidoarjo, 2019)
This research examined the relationship between five areas of cognitive autonomy and development among adolescents. Students from middle and high school in Keddah participated in this study. Ninety-four participants responded on the Cognitive Autonomy and Self-Evaluation (CASE) inventory, which examined the evaluative thinking, voicing opinions, comparative validation, decision making, and self-assessment. Scores were compared based on gender and grade. Results highlighted that high school students scored significantly higher in two of the five areas of cognitive autonomy. Additionally, females in middle school rated themselves significantly higher in two areas of cognitive autonomy (evaluative thinking and decision making). Areas of academic grades, time watching TV, time spent reading, and using computer were also discussed.